Vpliv menjave košarkarskih trenerjev na tekmovalno uspešnost ekipe - Vinazza, Anže (Šport (Ljubljana), 2019)
The study aimed to establish the number of replacements of basketball coaches during the competitive season as well as how such replacements affected the teams' performance. The focus of the study was on the 1st Slovenian Basketball League (1. SKL) and the Adriatic Basketball Association League (ABA League) in the 2014/2015, 2015/2016 and 2016/2017 competitive seasons. The numbers of coach replacements were also compared between both leagues. We established that lower-ranked teams replace their coach more often during the season than their higher-ranked counterparts. A comparison between coach replacements during and after the season reveals that the share of replacements during the season is slightly higher (this is particularly true for the ABA League). The differences in the number of replacements between both leagues exist but they are not considerable. The percentage of teams which decided to replace their coach during the season was slightly higher for the 1. SKL than for the ABA League. After the coach is replaced during the season, the teams' performance in terms of results mostly improves. With new coaches, the victory/defeat ratio after two, three, four and five matches improves compared to the respective ratio with old (previous) coaches during the last two, three, four and five matches before replacement.
Keywords: 1. SKL; ABA; basketball; coaches; ekipe; košarka; menjava trenerjev; sport; šport; teams; tekmovalna uspešnost; trenerji